Identification of Ear Morphology Genes in Maize (Zea mays L.) Using Selective Sweeps and Association Mapping - Li, Ting; Qu, Jianzhou; Tian, Xiaokang; Lao, Yonghui; Wei, Ningning; Wang, Yahui; Hao, Yinchuan; Zhang, Xinghua; Xue, Jiquan; Xu, Shutu (Frontiers in Genetics, 2020)
The performance of maize hybrids largely depend on two parental inbred lines. Improving inbred lines using artificial selection is a key task in breeding programs. However, it is important to elucidate the effects of this selection on inbred lines. Altogether, 208 inbred lines from two maize heterosis groups, named Shaan A and Shaan B, were sequenced by the genotype-by-sequencing to detect genomic changes under selection pressures. In addition, we completed genome-wide association analysis in 121 inbred lines to identify candidate genes for ear morphology related traits. In a genome-wide selection scan, the inbred lines from Shaan A and Shaan B groups showed obvious population divergences and different selective signals distributed in 337 regions harboring 772 genes. Meanwhile, functional enrichment analysis showed those selected genes are mainly involved in regulating cell development. Interestingly, some ear morphology related traits showed significant differentiation between the inbred lines from the two heterosis groups. The genome-wide association analysis of ear morphology related traits showed that four associated genes were co-localized in the selected regions with high linkage disequilibrium. Our spatiotemporal pattern and gene interaction network results for the four genes further contribute to our understanding of the mechanisms behind ear and fruit length development. This study provides a novel insight into digging a candidate gene for complex traits using breeding materials. Our findings in relation to ear morphology will help accelerate future maize improvement.